Challenges of Transitioning to e-learning System with Learning Objects Capabilities - Miroslava Raspopovic (Athabasca University Press, 2016)
In order for higher education institutions, which implements blended and/or online learning to remain competitive and innovative it needs to keep up with the cutting edge technological and educational advances. This task is usually very difficult, keeping in mind the budget constraints that many institutions have. This usually implies that existing open source solutions have to be used and adapted to individual needs of each institution. Keeping up with the current technological advances often brings not only financial challenges, but also transitional challenges that may put at risk learning quality and reputation of the institution, as well as performance of students. This work describes the features of the system, results and challenges of transitioning to e-learning system that displays learning materials through sequence of reusable learning objects (LOs) from the system that does not have these capabilities. The goal of such system is to increase reusability of learning content, and moreover, to increase online interactivity and communication between the instructor and students. Findings of this work reveal advantages, disadvantages and potential obstacle of implementation e-learning system with LOs and give an overview of suggestions for implementation improvements. These suggestions are given based on evaluation of implementation of new e-learning system with LOs, after the transition from the traditional e-learning system. Furthermore, based on the research of existing methodologies in the field of information systems, and the results of this research, this work proposes methodology for transferring into e-learning system with LOs.